Mitotic activation of the kinase Aurora-A requires its binding partner Bora. - Hutterer, A.; Berdnik, D.; Wirtz-Peitz, F.; Zigman, M.; Schleiffer, A.; Knoblich, J.A. (Developmental Cell, 2006)
The protein kinase Aurora-A is required for centrosome maturation, spindle assembly, and asymmetric protein localization during mitosis. Here, we describe the identification of Bora, a conserved protein that is required for the activation of Aurora-A at the onset of mitosis. In the Drosophila peripheral nervous system, bora mutants have defects during asymmetric cell division identical to those observed in aurora-A. Furthermore, overexpression of bora can rescue defects caused by mutations in aurora-A. Bora is conserved in vertebrates, and both Drosophila and human Bora can bind to Aurora-A and activate the kinase in vitro. In interphase cells, Bora is a nuclear protein, but upon entry into mitosis, Bora is excluded from the nucleus and translocates into the cytoplasm in a Cdc2-dependent manner. We propose a model in which activation of Cdc2 initiates the release of Bora into the cytoplasm where it can bind and activate Aurora-A.